DIVERSI DALAM TINJAUAN USUL FIQH - Syamsuddin Sakka (IAIN Palopo, 2022)
Diversion is meant to divert children’s criminal offenses out of the criminal justice system. Persuasive action or non-penal approach and give the children the opportunity to correct mistakes as the main principles. The study aims to find the conformity of a diversion with Islamic law through the principles of Islamic Jurisprudence’s review. This research was library research in which the qualitative data inferred was analysed by using content analysis. This research finds that a diversion is very much in line with Islamic law based on the principles of Islamic Jurisprudence’s review. Children are included in the category of do not have the expertise (legally incompetent) or have rudimentary skills so that they cannot be subjected to the law like an adult. There are many propositions that reinforce the conformity of a diversion with Islamic law. The Qur'an provides solutions for the settlement of cases outside of the court (non-litigation) known as negotiation and mediation. There are several hadiths that explain the treatment of children who make mistakes up to the level of tazir sanctions which all stand on the principle of education to children. There are other propositions such as sadd al-dhara’i with the intention of blocking the harm and urf with the intention of solving cases using customary law and local wisdom of the community. The concept of a diversion is also related to some rules such as special applicable laws, opportunities to apologize for mistakes that were made for the first time, and other rules